Metabolomic Insights into the Allelopathic Effects of Ailanthus altissima (Mill.) Swingle Volatile Organic Compounds on the Germination Process of Bidens pilosa (L.) - Leonardo Bruno; Diana M. Mircea; Fabrizio Araniti (Metabolites)
Background/Objectives: This study explores the allelopathic effects of volatile organic compounds (VOCs) emitted by the invasive species Ailanthus altissima (Mill.) Swingle on the seed germination of Bidens pilosa. A. altissima is known for releasing allelopathic VOCs that suppress the growth of neighbouring plants, contributing to its invasive potential. Methods: To examine these effects, we exposed B. pilosa seeds to varying concentrations of A. altissima VOCs, assessing germination rates and metabolic changes through untargeted metabolomics. Results: Our findings revealed that VOCs from A. altissima significantly inhibited the germination speed and overall germination rates of B. pilosa in a dose-dependent manner. Metabolomic profiling showed disruptions in energy and amino acid metabolism pathways, specifically involving delayed breakdown of starch and key metabolites, indicating inhibition of critical metabolic processes during early germination stages. This metabolic delay likely impairs B. pilosa’s establishment and competitiveness, enhancing A. altissima’s ecological dominance. Conclusions: The results underscore the potential of VOC-based allelopathy as a mechanism of plant invasion, offering insights into the role of VOCs in interspecies plant competition and ecosystem dynamics.